Biological Effects of 5-Carboxy-2′-Deoxyuridine: Hydrolysis Product of 5-Trifluoromethyl-2′-Deoxyuridine - Clough, D. W. (1978)
5-Carboxy-2′-deoxyuridine (5-COOH-2′-dUrd) is a product of the base-catalyzed hydrolysis of 5-trifluoromethyl-2′-deoxyuridine. Hydrolysis of 5-trifluoromethyl-2′-deoxyuridine to 5-COOH-2′-dUrd in phosphate-buffered saline was kinetically first order and was pH dependent. At 37°C and pH 7.0, 7.5, and 8.0, hydrolysis occurred with rate constants of 4.19 × 10(−5), 9.30 × 10(−5), and 1.61 × 10(−4) s(−1), respectively, with corresponding half-lives of 45.7, 20.6, and 11.9 h. 5-COOH-2′-dUrd inhibited growth of HEp-2 cells by 21, 67, and 91% at 1.0, 10, and 100 μM, with no antiviral activity against herpes simplex virus type 1 or herpes simplex virus type 2 at 1.0 or 10 μM. Partial reversal of cytotoxicity in HEp-2 cells was achieved with orotidine, uridine, deoxythymidine, or deoxycytidine, whereas complete reversal of cytotoxic effects was achieved with simultaneous addition of deoxythymidine, deoxycytidine, and uridine. 5-COOH-2′-dUrd at 50 μM inhibited incorporation of [(14)C]orotate into RNA and DNA by 65 and 27%, respectively. 5-COOH-2′-dUrd had no effect on the incorporation of [(3)H]uridine into DNA or RNA. Because of the structural similarities to deoxythymidine, 5-COOH-2′-dUrd was tested as an inhibitor of deoxythymidine kinase. 5-COOH-2′-dUrd was neither a substrate nor an inhibitor of herpes simplex virus type 1 induced deoxythymidine kinase or HEp-2 cell deoxythymidine kinase. Based on these observations, the metabolic block induced by 5-COOH-2′-dUrd has been localized to the de novo pyrimidine biosynthetic pathway between orotate phosphoribosyl transferase and orotidine 5′-phosphate decarboxylase.